Innovation stimulants, innovation capacity, and the performance of capital projects - Chen, Hong Long (Journal of Business Economics and Management, 2014)
Abstract. Identifying the critical determinants of innovation performance is crucial. However, few studies explore and quantify systematically the relationships between innovation factors and the performance of capital projects. This study of 121 capital projects shows that the relationships among project innovation stimulants, innovation capacity, and project performance are indeed significant. Hierarchical robust regression analyses using a maximum R-square improvement procedure show that technology management has the highest effect on the variation in our project performance data. Validating out-of-sample data demonstrates that our optimal model explains 34.42% of the variation in the performance of capital projects. Ultimately, our findings suggest that project human factors are essential stimulants in innovation performance, which in turn affect the performance of capital projects. Our findings also reveal that the stimulant factors do not have a direct impact on capital project performance, but rather have an indirect impact via project innovation capacity.